Rehabilitation program and its effect on the efficiency of the knee joint after cross-linked ligament surgery - Khuraibet, Fatemah Assad (International Journal of Psychosocial Rehabilitation, 2019)
The rapid progress in training and its methods is one of the factors that contributed to the high rates of sports injury and its complications, especially injuries of the muscular and nervous system, due to the use of high intensity and for long periods with the absence of the correct codification of pregnancy in a manner consistent with the functional condition of the player. The injuries of the articular system are of concern to athletes, as the human movement in general and the sports movement in particular depends on the basic movements performed by the joints, so any injury in these joints hinders the athlete from successfully completing his motor tasks.